2019
DOI: 10.1126/sciadv.aax2211
|View full text |Cite
|
Sign up to set email alerts
|

Descending pathways mediate adaptive optimized coding of natural stimuli in weakly electric fish

Abstract: Biological systems must be flexible to environmental changes to survive. This is exemplified by the fact that sensory systems continuously adapt to changes in the environment to optimize coding and behavioral responses. However, the nature of the underlying mechanisms remains poorly understood in general. Here, we investigated the mechanisms mediating adaptive optimized coding of naturalistic stimuli with varying statistics depending on the animal’s velocity during movement. We found that central neurons adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…Indeed, recent studies have shown that the statistics of movement envelopes will change as a function of the animal's environment (Huang et al . 2019). Specifically, these are determined from the relative movement between two or more conspecifics; the animal's level of activity will strongly determine how steeply spectral power decays with increasing temporal frequency (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies have shown that the statistics of movement envelopes will change as a function of the animal's environment (Huang et al . 2019). Specifically, these are determined from the relative movement between two or more conspecifics; the animal's level of activity will strongly determine how steeply spectral power decays with increasing temporal frequency (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important as previous studies have shown that a strong factor contributing to PCell heterogeneities is the amount of descending input (i.e., feedback) that is received from higher brain centers. The effect of such feedback has been mostly studied at the single neuron level (Bastian, 1986;Chacron et al, 2005b;Marsat and Maler, 2012;Huang et al, 2018Huang et al, , 2019Metzen et al, 2018) and further studies are needed to understand whether and, if so, how such feedback can facilitate detection of EA synchrony by ELL PCells.…”
Section: Feature Invariant Representations Of Natural Electrocommunicmentioning
confidence: 99%
“…Glutamate (1 mM; Sigma-Aldrich) and serotonin (1 mM; Sigma-Aldrich) were dissolved in saline (111 mM NaCl, 2 mM KCl, 2 mM CaCl 2 , 1 mM MgSO 4 , 1 mM NaHCO 3 and 0.5 mM NaH 2 PO 4 ; Sigma-Aldrich) for application. Drug application electrodes were made using either two-barrel (for electrophysiology) or single-barrel (for behavior) glass micropipettes as described previously (Huang et al, 2018 , 2019 ; Marquez and Chacron, 2018 , 2020b ; Metzen et al, 2018 ). For single neuron recordings, two-barrel pipettes were used for independent application of serotonin or glutamate in the vicinity of the neuron being recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, when two fish are located close to one another (i.e., <1 m apart), interference between their EODs gives rise to sinusoidal amplitude modulation (AM) whose frequency is given by the difference between the EOD frequencies. Changes in the relative orientation and distance between both animals give rise to changes in the amplitude (i.e., the envelope) of the sinusoidal amplitude modulation (Yu et al, 2012 ; Fotowat et al, 2013 ; Metzen and Chacron, 2014 ; Huang et al, 2019 ). As such, the frequency components of the envelope are directly associated with the statistics of the relative movement between fish.…”
Section: Introductionmentioning
confidence: 99%